Writing in psychology a student guide - Smyth, T. Raymond (John Wiley & Sons, 1996)
This book assists in the process of writing formal and/or technical papers. It is consistent with the guidelines outlined in the Publication Manual of the American Psychological Association Fourth Edition. It has an accessible three-part construction: writing and the preparation of research papers, preparation of research reports and the fundamental aspects of writing and presentation. In addition, it has complete coverage of the use, preparation and presentation of figures and tables and contains advice on grammar, punctuation and spelling. Contains sample papers so readers can see accurate as well as inaccurate examples.